Development patterns of the strategic management of transport enterprises - Шарко, Маргарита Васильевна (Technology audit and production reserves, 2016)
Market transport services trends, allowing to identify the positive impact of the transport sector development to ensure socio-economic development of the state are analyzed. Dynamics of cargo and transport is provided. Identification of problems and obstacles of transport services market development is presented. Specific conditions of transport companies operation in case of dynamic changes in the environment lead to the need to develop a strategic transportation management structure research. Circuit structure of the strategic transport enterprises management and development of the basic strategies to improve the validity of management decisions is presented. The main directions of transport services market development are designed. There are innovative development of production facilities, including maintenance and transportation, strengthening market position, increasing the level of competitiveness, compliance with quality standards, adaptation to the requirements of consumers. The necessity to respect the balance between transport traffic and service to maximize profits of transport companies is justified. Provided strategic transport enterprises management structure with its implementation could serve as a basis for increasing the efficiency of transport systems management development.